Hipomagnesemia como factor de riesgo para desarrollar dolor agudo en postoperados de colelitiasis - Isla Saavedra, Cecilia Palmira Del Carmen (2014)
INTRODUCTION: Magnesium is the fourth most abundant cation in the body, that is involving in more than 300 enzymatic reactions in numerous physiological functions and in the pathophysiology of many diseases affecting the surgical patient, is related to the physiology of pain by the NMDA receptors which are physiologically blocked by this ion. A noxa or painful stimulus maintained, increased levels of glutamate and substance P being able to remove the magnesium ion and facilitate depolarization NMDA receptor triggered and an increase in intracellular Ca2 + and activation of a number of enzyme systems leading to a state neuronal hyperexcitability and facilitates maintaining nociceptive transmission. MATERIALS AND METHODS: One of a prospective observational cohort study, which included a case group and a control every 42 patients each group; both groups were measured in serum magnesium levels before entering surgery and after this we applied the visual analog scale to measure pain levels immediately showed off operating room at 2, 4 , 8, 12 and 24 hours. RESULTS: We found statistically significant, with p <0.05 and 95% CI that hypomagnesemia is a risk factor immediately off operating room (RR: 2.55), at 4 (RR: 1.21), 8 (RR: 2.33) and 12 (RR: 6.80) hours postoperatively and a partnership to 24 hours. CONCLUSIONS: Hypomagnesemia is a risk factor for developing acute postoperative pain immediately off operating room, at 4, 8 and 12 hours after surgery and a partnership to 24 hours.